Change in the muscle activity of the lower limbs of hockey players in the phases of acceleration and uniform skating - Volobuev, A.L.; Ponimasov, O.E.; Mironov, A.O.; Gerasimov, A.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to study the changes in the muscle activity of the lower limbs of hockey players in the phases of acceleration and uniform skating during forward movement. Methods and structure of the study. The hockey players performed skating at maximum speed over a distance of 30 m from a stationary position at the start. Muscle activity was measured on the basis of the registration of EMG signals in the acceleration phase and the uniform skating phase. The EMG waves of each muscle were normalized relative to the peak step intensity in the steady-state mode. Results and conclusions. The main factor influencing the push-off forces in the acceleration phase is the activity of the medial gastrocnemius muscle. During uniform skating, the increased activity of the vastus lateralis and vastus medialis muscles provides a greater speed of extension and a greater skating speed.